Lipid profiles of human milk and infant formulas: a comparative lipidomics study - Wu, Danjie; Zhang, Le; Zhang, Yan; Shi, Jiachen; Tan, Chin Ping; Zheng, Zhaojun; Liu, Yuanfa (Multidisciplinary Digital Publishing Institute, 2023)
Infant formulas (IFs) are prevalent alternatives for human milk (HM), although their comparative lipid profiles have not been fully investigated. We adopted lipidomics to analyze and compare in-depth the lipid patterns of HM and IFs. The results indicated that the distribution of fatty acids (FAs) and the structure of triacylglycerols varied substantially in the analyzed samples. A total number of 425 species were identified during the analysis. HM was abundant in triacylglycerols that contained unsaturated and long-chain FAs (>C13), while triacylglycerols in IFs were mainly comprised of saturated and medium-chain FAs (C8−C13). Higher levels of sphingomyelin were observed in HM. Furthermore, HM and IF1 contained 67 significantly differential lipids (SDLs), and 73 were identified between HM and IF2. These SDLs were closely associated with nine metabolic pathways, of which the most significant was the glycerophospholipid metabolism. The results shed light on the differences between the lipid profiles of human and infant formula milks, and provide support for designing Chinese infant formula.